Household Saving in France : Stochastic Income and Financial Deregulation - Levy, Joaquim; Ostry, Jonathan (Washington, D.C. : International Monetary Fund, 1994)
The household saving ratio in France has undergone very sharp changes over the past two decades, falling dramatically in the first part of the 1980s before rising in more recent years. This paper emphasizes two factors in the evolution of private saving in France. The first relates to perceptions of household income growth and uncertainty, which are likely to have been affected by deteriorating labor market conditions, and which may therefore help to account for the recent increase in saving. The second factor relates to financial deregulation which may have lowered saving and increased its sensitivity to interest rate changes. It is argued that both factors have played some role in the evolution of French household saving.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet